2017
DOI: 10.17116/klinderma201716632-37
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of skin diseases in Stavropol territory in 2010—2016

Abstract: Актуальность изучения эпидемиологических характеристик болезней кожи и подкожной клетчатки высока ввиду их большой распространенности, которая имеет региональные особенности. Цель исследования-анализ дерматологической заболеваемости в Ставропольском крае за период с 2010 по 2015 г. Материал и методы. Материалом исследования послужили данные официального статистического наблюдения о числе заболеваний, зарегистрированных в Ставропольском крае, с применением математического и описательного методов статистического… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…(from 0·18% to 0·28% between 2000 and 2013) reported a steadily increasing trend in psoriasis prevalence in Canada and Taiwan, respectively (Table S6; see Supporting Information). A similar pattern of a steadily increasing trend in psoriasis prevalence in individuals of all ages has been reported in Germany,41 Israel,15 Korea,95,96 Russia,92,93,94 Taiwan97 and the UK43 (Table S7; see Supporting Information).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…(from 0·18% to 0·28% between 2000 and 2013) reported a steadily increasing trend in psoriasis prevalence in Canada and Taiwan, respectively (Table S6; see Supporting Information). A similar pattern of a steadily increasing trend in psoriasis prevalence in individuals of all ages has been reported in Germany,41 Israel,15 Korea,95,96 Russia,92,93,94 Taiwan97 and the UK43 (Table S7; see Supporting Information).…”
Section: Resultssupporting
confidence: 77%
“…When examining trends in psoriasis incidence over time in people of all ages, data from Germany, 41 the Netherlands, 90 Israel, 15,91 the UK 43 and Russia [92][93][94] demonstrate that psoriasis incidence either remains fairly stable or decreases slightly over time. However, in Denmark the incidence of psoriasis in people of all ages has been inconsistent over time, with a decrease in incidence from 140Á1 to 104Á0 per 100 000 person-years between 2003 and 2005, followed by an increase to 181Á0 per 100 000 person-years in 2010, which then decreased to 151Á2 per 100 000 person-years in 2012 (Table 4).…”
Section: Variation In Incidence and Prevalence Over Timementioning
confidence: 99%
“…The 23 studies that reported on the incidence of psoriasis in the general population were conducted mainly in western and eastern Europe (16 studies), and North America (six studies). Twelve studies reported on the incidence of psoriasis in all ages, with the incidence of the disease varying from 31.4 per 100 000 person years in eastern Europe (Russia)16 to 521.1 per 100 000 person years in western Europe (Germany) 17. Springate and colleagues3 reported a slight decline in the incidence of psoriasis in all ages in the United Kingdom (from 159.0 to 129.0 per 100 000 person years between 1999 and 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In Saudi Arabia; Fatani, Mohamad I et al [3] reported incidence around 5.3%. This was higher than reported in Russia 31.4 per 100 000 person years [15] and comparable to Germany 521.1 per 100 000 person years [16]. Springate and colleagues [17] reported a slight decline in the incidence of psoriasis in all ages in the United Kingdom from 159.0 to 129.0 per 100 000 person years between 1999 and 2013).…”
Section: Discussionmentioning
confidence: 72%